Thyroid Hormone Signaling and Adult Neurogenesis in Mammals - Remaud, Sylvie; Gothié, Jean-David; Morvan-Dubois, Ghislaine; Demeneix, Barbara A. (Frontiers in Endocrinology, 2014)
The vital roles of thyroid hormone in multiple aspects of perinatal brain development have been known for over a century. In the last decades, the molecular mechanisms underlying effects of thyroid hormone on proliferation, differentiation, migration, synaptogenesis and myelination in the developing nervous system have been gradually dissected. However, recent data reveal that thyroid signalling influences neuronal development throughout life, from early embryogenesis to the neurogenesis in the adult brain. This review deals with the latter phase and analyses current knowledge on the role of T3, the active form of thyroid hormone, and its receptors in regulating neural stem cell function in the hippocampus and the subventricular zone, the two principal sites harbouring neurogenesis in the adult mammalian brain. In particular, we discuss the critical roles of T3 and TRα1 in commitment to a neuronal phenotype, a process that entails the repression of a number of genes, notably that encoding the pluripotency factor, Sox2. Furthermore, the question of the relevance of thyroid hormone control of adult neurogenesis is considered in the context of brain aging, cognitive decline and neurodegenerative disease.